Implementasi Kesehatan Dan Keselamatan Kerja Pada Atraksi Wisata Paralayang Di Desa Kutuh, Kabupaten Badung - Priesca Priesca; I Gede Anom Sastrawan (JURNAL DESTINASI PARIWISATA, 2019)
This study aims to find out how the implementation of occupational health and safety of paragliding tourist attraction management system in Timbis Cliff, Kutuh Village, Badung Regency. The technique that used are observation technique, interview, literature study, and documentation study. While analysis technique that used are qualitative description. The data on this research based on interview result from the informant, which is key informant or base informant on the main research field. The result of the interview is how the paragliding management implemented the occupational health and safety to the paragliding instructor team and the tourist, the factors that influenced the accidental issues, which is internal factors or external factors which is happened when the paragliding take place, also, how the management staff prevented and mitigated the accident when it happened. According to the data, the management staff implemented terms and condition before doing paragliding activity according to Standard Operational Procedure (SOP) like before being an instructor for paragliding, the person must have minimal Tandem 2 licence to be an instructor, maintenance and testing the equipment before using them, giving a short briefing to the tourist to prevent them doing anything forbidden and to avoid accident Keywords: Occupational Health and Safety, Paragliding, Timbis Cliff, Standard Operational Procedure, Accident, Safety and Health